Implementation of Blood-Boosting Tablet Distribution for Adolescent Girls as an Effort to Prevent Anemia - Arnita Julianti; Novita Rany; Haili (Viva Medika, 2024)
Anemia is one of the health problems worldwide, especially in developing countries, where an estimated 30% of the world's population suffers from it. The aim of this research activity is to understand the implementation of blood-boosting tablet distribution. The method used is qualitative, involving the USG stage to determine problem priorities, followed by SWOT analysis. The sample for this research report consists of high school female students. The next stage involves conducting counseling sessions according to the identified problem priorities. The activity took place at the Hulu Tembilahan Community Health Center in the Indragiri Hilir District from November 4th to December 18th, 2023. Through a well-organized series of stages, from preparation to conclusion, this activity successfully created a positive dialogue space between organizers and participants. The results indicated suboptimal implementation of distributing blood-boosting tablets for adolescent girls at the Hulu Tembilahan Community Health Center in the Indragiri Hilir District and identified problem priorities. The Plan of Action involves Health Education by healthcare professionals as an effort to increase the launch/commitment to anemia-free initiatives in the preventive implementation of anemia among adolescent girls.